Emotional Speaker Identification From The Vocal Characteristics - Malika Akak; Halim Sayoud (Al-Lisaniyyat, 2014)
This paper presents the identification of emotional state of the speaker from a variety of database given. Eleven prosodic parameters have been proposed for features extraction and statistical techniques are used to minimize the amount of data to be handled